The current recommendation for isolation in COVID-19 infection: A perspective review article - Das, Sunil Kumar; Sah, Sunny Kumar; Yadav, Manish (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: There have been multiple variants of Severe acute respiratory syndrome coronavirus 2 (SARS CoV- 2), a strain of coronavirus, that causes COVID-19, a respiratory illness responsible for the ongoing COVID-19 pandemic, since its first identified outbreak in Wuhan, China in November 2019. Since the pandemic began there have been various changes in the isolation period of the identified cases reducing from 2 to 3 weeks to the current recommendation of 5 days of isolation in symptom-free individuals in various countries. As of July 2022, only the Omicron variant has been identified as a variant of concern by the World Health Organization.Method: Articles were searched in Google scholar, PubMed, CDC guidelines, NHS guidelines (UK), Indian guidelines (Ministry of Health and Family Welfare), Nepal guidelines (Ministry of Health and Population), and WHO guidelines.Result: The guidelines recommend a self-isolation period of infected individuals ranging from 5 to 14 days after testing positive for the COVID-19 disease.Conclusion: COVID-19 is here to stay and showing no signs of slowing down though overall fatality rate have been on decline owing to vaccination and increased immunity against the virus, it is ideal to shorten the duration of isolation and focus on protection against the virus all the times and not letting the guard down.